Cancer Risk of Low Dose Ionizing Radiation - Ali, Yasser F.; Cucinotta, Francis A.; Ning-Ang, Liu; Zhou, Guangming (Frontiers in Physics, 2020)
The radiation exposure of individuals has been on the rise due to an increased amount of radiation use, e.g., in medicine for diagnostic imaging and treatment procedures, industrial applications including military defense activities and nuclear power plants, and in academics for educational and scientific research. Space exploration missions and space tourism are additional areas of protracted low dose exposure situations with radiation types not present on the Earth. In contrast to high doses of ionizing radiation, cancer risk assessment of the more commonly encountered or protracted radiation exposure is still under debate and uncertainty making it fuzzy area. A major challenge lies in providing a scientific basis to estimate low dose radiation carcinogenesis risks. In this review we aim, through the collected epidemiological and experimental studies' data, to address the central questions in radiological protection; including quantification of the risks and uncertainties from low doses of ionizing radiation and what is a sound scientific consensus to advise on risk perception for low dose radiation exposure.